STRATEGIES FOR IMPROVING QUALITY OF HUMAN RESOURCES MANAGEMENT IN GUANGXI UNIVERSITIES - Juan, Huang; Suteeniran, Niran; Dejhome, Pachara; Setkajorn, Sarayut; Wimuttipanya, Jittawisut (Journal of MCU Nakhondhat, 2024)
This research aimed to study the strategies for improving the quality of human resource management in Guangxi University. This research was a mixed method research. The population used in the research was 285 middle managers, selected by purposive sampling from six different types of public undergraduate universities in the Beibu Gulf Economic Zone, Guangxi. The research instrument was a questionnaire with a reliability of 0.92. Data were analyzed using percentages, means, standard deviations, and content analysis. The results revealed the following: 1) The current situation of human resource management in Guangxi University in five aspects is at a high level. The research results in this area are from highest to lowest as follows: The level of recruitment management is at the highest level (μ = 3.98), followed by training management and performance management (μ = 3.94), and the level of compensation and welfare management is at the lowest level (μ = 3.91). 2) The strategies for improving the quality of human resource management in Guangxi University consist of 5 issues: 1) Recruitment management with 6 measures, 2) Training management with 6 measures, 3) Performance management with 6 measures, 4) Compensation and welfare management with 6 measures, and 5) Employee relationship management, consisting of 6 measures, totaling 30 measures. The appropriateness and feasibility of the strategies for improving the quality of human resource management indicate a high level of appropriateness and feasibility of the strategies. The strategy of excellent organizational management through the development and improvement of the quality of human resources is considered an important mechanism for developing a quality organization to its full potential and creating an innovative society for sustainable problem solving.